Influencia de la violencia intrafamiliar en el nivel académico de un estudiante - Collantes Cepeda, Daryl Brithany (2020)
Family violence produces problems of behavioral, social and emotional adjustment, which translate into antisocial behavior in general, depression and anxiety and problems at school. The problems of behavioral and social adjustment are manifested in different areas of drug use, academic orientation and criminal behavior. This case study was conducted in order to determine the influence of domestic violence on a student's academic level. Different types of psychological techniques were used in conjunction with the interview to arrive at a diagnostic assessment. The tests that were used were the HTP and the Beck Depression Inventory, to evaluate the depression rates, helping all the information collected from the interview. Psychological